2015
DOI: 10.1111/ajco.12329
|View full text |Cite
|
Sign up to set email alerts
|

Could yoga practice improve treatment‐related side effects and quality of life for women with breast cancer? A systematic review and meta‐analysis

Abstract: The current evidence demonstrates that yoga practice could be effective in enhancing health and managing some treatment-related side effects for patients recovering from breast cancer. In future clinical studies, clinicians should consider the patient's wishes along with the current best evidence of the effects of yoga practice in their clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 41 publications
3
85
0
1
Order By: Relevance
“…The participants reported that previous problems, such as amnesia, headaches, tightness, pain in the limbs, swollen limbs, and fatigue were alleviated. This is consistent with the results of other yoga studies that reported reduced pain, anxiety and swelling; increased energy, flexibility, and physical function; a sense of control; feelings of comfort and relaxation; and the ability to maintain self-control [20][21][22]. In particularly, a previous study reported that the participants who provided positive feedback on healing yoga stated that it enabled them to enjoy the exercise process [20].…”
Section: Discussionsupporting
confidence: 89%
“…The participants reported that previous problems, such as amnesia, headaches, tightness, pain in the limbs, swollen limbs, and fatigue were alleviated. This is consistent with the results of other yoga studies that reported reduced pain, anxiety and swelling; increased energy, flexibility, and physical function; a sense of control; feelings of comfort and relaxation; and the ability to maintain self-control [20][21][22]. In particularly, a previous study reported that the participants who provided positive feedback on healing yoga stated that it enabled them to enjoy the exercise process [20].…”
Section: Discussionsupporting
confidence: 89%
“…However, that systematic review was limited to studies published no later than 2010 and was also limited to the two component scores only. A final, and more recent meta-analysis, examined yoga's pooled effects on HRQOL among women with breast cancer [24]. Although an overall yoga and HRQOL effect was noted in this study, final results were mixed due to positive effects seen by the control over yoga on physical health.…”
Section: Discussionmentioning
confidence: 77%
“…Many meta-analysis have shown the potential benefits of yoga on measures of HRQOL in numerous clinical populations [22,23,24]. However, although there has been research done on the effects of yoga on measures of HRQOL, none to date have measured the overall effect size of yoga on HRQOL measured by the SF-36/12.…”
Section: Exercise Medicinementioning
confidence: 99%
“…Moreover, broad acceptance has developed for mind body concepts with elements of Thai Chi or Yoga. Positive results with respect to fatigue and other symptoms have been described (15,16). Yet, it has to be noticed that these Asian Movement concepts differ widely in their execution form more meditative to more power-oriented exercises.…”
Section: Discussionmentioning
confidence: 92%